Ethical issues in adaptive clinical trials - Hey, Spencer Phillips (Henry Stewart Talks, 2016)
Purported ethical advantages of adaptive clinical trial designs, Foundations of research ethics, Ethical tensions in randomized controlled trials, The concept(s) of equipoise, Do adaptive designs enhance patient-subject benefit?, The therapeutic misconception, Efficiency, Are adaptive randomized trials unjust?